Hubungan Program Radio “Genk Ladies” terhadap Pemenuhan Kebutuhan - Reni Renita; Nova Yuliati (Bandung Conference Series: Public Relations, 2022)
Abstract. Radio as a mass media that provides information, entertainment and education through transmission waves and is widespread. Over time, there have been many non-government or private radio stations in Indonesia accompanied by various radio segments. The growth of female radio in Indonesia provides many benefits for radio listeners with the female segmentation. One of the female radios in Bandung is B-Radio 95.6 FM Bandung which has a lot of broadcast programs such as “Genk Ladies” which provides information about entertainment news, gossip, and Indonesian and Korean songs. In preparing this report, quantitative research methods and correlational approaches were used to obtain data and information with a population of 9,286 people and 99 people as respondents. The data was collected by distributing questionnaires using random sampling technique. In this study using the theory of media exposure. Then, use the uses & gratifications proposed by Katz, Blumer, and Gurevitch. The purpose of this study was to determine the extent to which the radio broadcast of "Genk Ladies" B-Radio 95.6 FM Bandung as a sharing medium for women for listeners. The results of this study are the relationship between the "Genk Ladies" broadcast program and the fulfillment of the information needs of female listeners at B-Radio 95.6 FM Bandung. Produced a coefficient test of 0.843 with a relationship level of "Very Strong" with a positive and unidirectional coefficient. So it can be concluded that H0 is rejected and H1 is accepted that the broadcast program "Genk Ladies" has a relationship with meeting the information needs of female listeners at B-Radio 95.6 FM Bandung. Abstrak. Radio sebagai media massa yang memberikan informasi, hiburan, dan edukasi melalui gelombang transmisi dan tersebar luas. Seiring perkembangan waktu sudah banyak radio non-pemerintah atau swasta di Indonesia diiringi dengan segmentasi radio yang beragam. Tumbuhnya radio perempuan di Indonesia memberikan banyak manfaat bagi pendengar radio dengan segmentasi perempuan. Salah satu radio perempuan yang ada di Bandung adalah B-Radio 95,6 FM Bandung yang memiliki banyak sekali program siaran seperti “Genk Ladies” yang memberikan informasi mengenai berita entertainment, gossip, dan lagu Indonesia serta Korea. Dalam penyusunan laporan ini, menggunakan metode penelitian kuantitatif dan pendekatan korelasional untuk memperoleh data dan informasi dengan populasi sebanyak 9.286 orang dan dipilih sebanyak 99 orang sebagai responden. Pengumpulan data tersebut dilakukan dengan cara menyebarkan kuisioner menggunakan teknik random sampling. Pada penelitian ini menggunakan teori dari terpaan media. Lalu, menggunakan uses & gratification yang dikemukakan oleh Katz, Blumer, dan Gurevitch . Tujuan dari penelitian ini untuk mengetahui sejauh mana siaran radio “Genk Ladies” B-Radio 95,6 FM Bandung sebagai media sharing perempuan untuk pendengarnya. Hasil dari penelitian ini hubungan antara program siaran “Genk Ladies” dengan pemenuhan kebutuhan informasi pendengar perempuan B-Radio 95,6 FM Bandung. Menghasilkan uji koefisen sebesar 0,843 dengan tingkatan hubungan “Sangat Kuat” dengan koefisien positif dan searah. Sehingga dapat disimpulkan H0 ditolak dan H1 diterima bahwa program siaran “Genk Ladies” memiliki hubungan dengan pemenuhan kebutuhan informasi pendengar perempuan B-Radio 95,6 FM Bandung.